Slow responder against methotrexate 50 mg intramuscular in severe psoriatic patients: A case series - Kusumaningrum, Niken; Wicaksono, Danar; Winarni, Dwi Retno Adi; Wirohadidjojo, Yohanes Widodo; Radiono, Sunardi (Dermatology Reports, 2019)
Methotrexate is the drug of choice used on moderate to severe psoriasis. The limited availability of oral tablet methotrexate stimulates the initiation of the protocol therapy 50 mg intramuscular methotrexate weekly in six consecutive weeks for severe psoriasis cases. There were 30 cases treated using this treatment modality. Twenty-six cases (86%) showed a good response and achieved PASI-90(Psoriasis Area Severity Index-90), four cases (13%) showed a slow response and did not achieve PASI-90. This case report collected slow response cases and identified their risk factor of slow responsiveness with this treatment modality. The comorbidity condition like metabolic syndrome, drugs induced psoriasis, continuous trauma, the side effect of methotrexate administration (ulceration), or the possibility of allergic or irritant contact dermatitis from occupation are suspected to be the risk factor for slow responders in this treatment modality.